Parasitoid gene expression changes after adaptation to symbiont‐protected hosts. (20th September 2017) - Dennis, Alice B.; Patel, Vilas; Oliver, Kerry M.; Vorburger, Christoph
Abstract: Reciprocal selection between aphids, their protective endosymbionts, and the parasitoid wasps that prey upon them offers an opportunity to study the basis of their coevolution. We investigated adaptation to symbiont‐conferred defense by rearing the parasitoid wasp Lysiphlebus fabarum on aphids ( Aphis fabae ) possessing different defensive symbiont strains ( Hamiltonella defensa ). After ten generations of experimental evolution, wasps showed increased abilities to parasitize aphids possessing the H. defensa strain they evolved with, but not aphids possessing the other strain. We show that the two symbiont strains encode different toxins, potentially creating different targets for counter‐adaptation. Phenotypic and behavioral comparisons suggest that neither life‐history traits nor oviposition behavior differed among evolved parasitoid lineages. In contrast, comparative transcriptomics of adult female wasps identified a suite of differentially expressed genes among lineages, even when reared in a common, symbiont‐free, aphid host. In concurrence with the specificity of each parasitoid lineages' infectivity, most differentially expressed parasitoid transcripts were also lineage‐specific. These transcripts are enriched with putative venom toxins and contain highly expressed, potentially defensive viral particles. Together, these results suggest that wild populations of L. fabarum employ a complicated offensive arsenal with sufficient genetic variation for wasps to adapt rapidly and specifically to their hosts' microbial defenses.